Editors’ Introduction - Basu, Kaushik (Published by Oxford University Press on behalf of the World Bank, 2021)
This volume contains the Papers and Proceedings of the Annual Bank Conference on Development Economics (ABCDE) held on June 20–21, 2016, in Washington D.C. The theme of the conference was “Data and Development Economics.”